Different effects of foam rolling on passive tissue stiffness in experienced and nonexperienced athletes - Mayer, I.; Hoppe, M. W.; Freiwald, J.; Heiss, R.; Engelhardt, M.; Grim, C.; Lutter, C.; Huettel, M.; Forst, R.; Hotfie, T. (Journal of Sport Rehabilitation, 2020)
Context: Foam rolling (FR) has been developed into a popular intervention and has been established in various sports disciplines. However, its effects on target tissue, including changes in stiffness properties, are still poorly understood. Objective: To investigate muscle-specific and connective tissue-specific responses after FR in recreational athletes with different FR experience. Design: Case series. Setting: Laboratory environment. Participants: The study was conducted with 40 participants, consisting of 20 experienced (EA) and 20 nonexperienced athletes (NEA). Intervention: The FR intervention included 5 trials per 45 seconds of FR of the lateral thigh in the sagittal plane with 20 seconds of rest between each trial. Main Outcome Measures: Acoustic radiation force impulse elastosonography values, represented as shear wave velocity, were obtained under resting conditions (t0) and several times after FR exercise (0 min [t1], 30 min [t2], 6 h [t3], and 24 h [t4]). Data were assessed in superficial and deep muscle (vastus lateralis muscle; vastus intermedius muscle) and in connective tissue (iliotibial band). Results: In EA, tissue stiffness of the iliotibial band revealed a significant decrease of 13.2% at t1 (P = .01) and 12.1% at t3 (P = .02). In NEA, a 6.2% increase of stiffness was found at t1, which was not significantly different to baseline (P = .16). For both groups, no significant iliotibial band stiffness changes were found at further time points. Also, regarding muscle stiffness, no significant changes were detected at any time for EA and NEA (P > .05). Conclusions: This study demonstrates a significant short-term decrease of connective tissue stiffness in EA, which may have an impact on the biomechanical output of the connective tissue. Thus, FR effects on tissue stiffness depend on the athletes` experience in FR, and existing studies have to be interpreted cautiously in the context of the enrolled participants.